2017
DOI: 10.1038/npp.2017.27
|View full text |Cite
|
Sign up to set email alerts
|

Garcinol Blocks the Reconsolidation of Multiple Cocaine-Paired Cues after a Single Cocaine-Reactivation Session

Abstract: Manipulations of memory reconsolidation can interfere with the ability of a drug-paired cue to drive drug-seeking behavior. However, the typical reconsolidation paradigm that reactivates the memory through the presentation of the cue (conditioned stimulus (CS)) only interferes with the memory of the reactivated CS while leaving other drug-paired CSs intact and able to continue driving drug-seeking behavior. Here, we used a novel unconditioned-stimulus (US) reactivation paradigm to interfere with the ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…Together, the results from the current study and other studies (22,23,29) support the idea that UCS memory retrieval–reconsolidation interference procedures have superior relapse-prevention characteristics compared with the classical CS memory retrieval–reconsolidation interference procedures.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Together, the results from the current study and other studies (22,23,29) support the idea that UCS memory retrieval–reconsolidation interference procedures have superior relapse-prevention characteristics compared with the classical CS memory retrieval–reconsolidation interference procedures.…”
Section: Discussionsupporting
confidence: 87%
“…We showed that in rats our procedure prevented both nicotine preference and nicotine relapse after both short and prolonged abstinence and that in humans the procedure prevented craving induced by diverse smoking-associated CSs (23). Dunbar and Taylor also recently reported that a drug named garcinol blocks the reconsolidation of multiple cocaine-paired cues after UCS reactivation (29). …”
mentioning
confidence: 99%
“…For example, a single US-reactivation session followed by pharmacological treatment in a rodent model of cocaine self-administration blocks cue-induced reinstatement to multiple CSs paired with the drug (Dunbar and Taylor Under Review). The pharmacological agent used was garcinol, a naturally-occurring histone acetyltransferase inhibitor that can safely be given to humans and also blocks reconsolidation after CS reactivation (Monsey et al 2016; Maddox et al 2013).…”
Section: Limitations Of the Clinical Application Of Reconsolidationmentioning
confidence: 99%
“…Based on preclinical studies of drug memories, the pharmacological approach may be more advantageous as compared to retrieval-extinction, as it requires only one short treatment session (Dunbar and Taylor Under Review; Luo et al 2015). Developing an effective clinical treatment that requires fewer sessions and less time will increase patient retention, decrease costs, and improve treatment outcomes.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation